Development of Fractional Domino Card Media in Mathematics Learning at Islamic Elementary School - Farikhatuzzaeniti, Nadiya Mutiara; Purwanti, Kristi Liani (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to develop appropriate media by measuring the validity of fractional domino media on fractional material. The type of research used in this research is research and development using the model proposed by Borg and Gall with ten stages, but due to the limited research time imposed by the school, the researchers only carried out eight stages (problems and potential, data collection, product design, expert validation, design revision, product trial, product revision, and trial use). This media focuses on fractional material presented in the form of illustrated images of fractional numbers. This media is made to foster interest in and improve student learning outcomes in mathematics. The data Subjects of this study were 28 students of class III MI Nyatnyono 02, and this sampling technique used a purposive sampling technique. The secondary data in this study were in the form of books, journal references, and the relevance of previous research studies, while the primary data were in the form of interviews, media validation, and student test results. The instruments used were material and media expert validation sheets, as well as tests given to students. The results of the study were (1) the average score of student learning outcomes using fractional domino cards with a percentage of 93%, (2) the average score of material expert validation with a percentage of 94% which is in the very feasible category ( 3) the average score of expert validation media with a percentage of 94%. The conclusion of the research is that the development of Fractional Domino Card media can be declared